CBCT findings in a case of triple mental foramina: a rare anatomic variation - Bianca Rodrigues Terrabuio; Mariela Peralta-Mamani; Juliana Bullen Rubira; Cássia Maria Fischer Rubira; Izabel Regina Fischer Rubira-Bullen (Revista Sul-Brasileira de Odontologia, 2025)
The mental foramen is located bilaterally on the anterior surface of the mandible. It serves as a reference point in the anesthetic technique used for blocking the mental nerve. It is important in planning implant placement and other surgical procedures in the region, to avoid damaging the mental vascular[1]nervous bundle. Case report: The present study presents a case of unilateral triple mental foramina, an anatomical variation with low incidence (0.7% to 1.2%), found incidentally in a cone beam computed tomography examination. Conclusion: despite the low incidence of the triple mental foramina, dentists must be aware of this anatomical variation to avoid complications during procedures.